All‐Component Transient Lithium‐Ion Batteries. Issue 10 (7th March 2016) - Fu, Kun (Kelvin); Wang, Zhengyang; Yan, Chaoyi; Liu, Zhen; Yao, Yonggang; Dai, Jiaqi; Hitz, Emily; Wang, Yibo; Luo, Wei; Chen, Yanan; Kim, Myeongseob; Hu, Liangbing
Abstract : Transient energy storage is a novel concept of using transient technology to design a device that can degrade and dissolve into the surrounding environment after being triggered by the external stimulus. A systematic design of a transient lithium‐ion battery to achieve high battery performance and all‐component transience is reported.